Methodological Approaches to Measuring Structural Convergence - Raleva, Stela (Research Papers, 2021)
The paper aims to present a systematic arrangement of the most important methodological approaches to measuring the structural convergence and to study their main characteristics. Much attention is directed to the approach of identifying the catch-up process and the distributional approach which are related to the evaluation of the β and σ convergences. The most significant advantages and drawbacks of these approaches are summarized and some of the most commonly implemented in them specific methods are discussed. The time series analysis and the cluster analysis are summarized focusing on their strong and weak aspects considered from methodological and cognitive point of view.
Keywords: Structural convergence; Catching-up process identification approach; Distributional approach; Time series approach; Cluster analysis approach